Ca2+ signalling is critical for autoantibody‐induced blistering of human epidermis in pemphigus. (1st September 2021) - Schmitt, T.; Egu, D.T.; Walter, E.; Sigmund, A.M.; Eichkorn, R.; Yazdi, A.; Schmidt, E.; Sárdy, M.; Eming, R.; Goebeler, M.; Waschke, J.
Summary: Background: Pemphigus is a severe bullous autoimmune skin disease. Pemphigus foliaceus (PF) is characterized by antidesmoglein (Dsg) 1 IgG causing epidermal blistering; mucosal pemphigus vulgaris (mPV) by anti‐Dsg3 IgG inducing erosions in the mucosa; and mucocutaneous pemphigus vulgaris (PV) by affecting both, with autoantibodies targeting Dsg1 and Dsg3. Objectives: To characterize the Ca 2+ flux pathway and delineate its importance in pemphigus pathogenesis and clinical phenotypes caused by different antibody profiles. Methods: Immunoprecipitation, Ca 2+ flux analysis, Western blotting, immunofluorescence staining, dissociation assays and a human skin ex vivo model were used. Results: PV IgG and PF IgG, but neither Dsg3‐specific monoclonal antibody (AK23) nor mPV IgG, caused Ca 2+ influx in primary human keratinocytes. Phosphatidylinositol 4‐kinase α interacts with Dsg1 but not with Dsg3. Its downstream target – phospholipase‐C‐γ1 (PLC) – was activated by PV IgG and PF IgG but not AK23 or mPV IgG. PLC releases inositol 1, 4, 5‐trisphosphate (IP3) causing IP3 receptor (IP3R) activation and Ca 2+ flux from the endoplasmic reticulum into the cytosol, which stimulates Ca 2+ release‐activated channels (CRAC)‐mediated Ca 2+ influx. Inhibitors against PLC, IP3R and CRAC effectively blocked PV IgG and PF IgG‐induced Ca 2+ influx; ameliorated alterations of Dsg1 and Dsg3 localization, and reorganization of keratin and actin filaments; and inhibited loss of cell adhesion in vitro . Finally, inhibiting PLC or IP3R was protective against PV IgG‐induced blister formation and redistribution of Dsg1 and Dsg3 in human skin ex vivo . Conclusions: Ca 2+ ‐mediated signalling is important for epidermal blistering and dependent on the autoantibody profile, which indicates different roles for signalling complexes organized by Dsg1 and Dsg3. Interfering with PLC and Ca 2+ signalling may be a promising approach to treat epidermal manifestations of pemphigus.